An IN VIVO bioequivalence study of two film-coated tablet formulations containing amoxicillin (875 mg) and clavulanic acid (125 mg) - Hai, Vu Xuan; Thanh, Nguyen Phuong; Anh, Pham Thi Van; Thao, Bui Thi Huong; Dung, Nguyen Chi; Linh, Hoang Van; Huyen, Nguyen Ta Mai; Hiep, Tran Tuan; Linh, Le Viet; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2026)
This was an open-label, randomized, two-treatment, two-sequence, two-period, single-dose crossover study conducted under fasting conditions in 36 healthy volunteers to assess bioequivalence of two film-coated tablet formulations containing amoxicillin 875 mg and clavulanic acid 125 mg. Participants were randomly assigned to receive either the test or the reference formulation containing 875 mg of amoxicillin and 125 mg of clavulanic acid in each study period. A washout interval of six days was applied between the two periods. Blood samples were collected prior to dosing and up to 8 hours post-administration. Plasma concentrations of amoxicillin and clavulanic acid were quantified using a liquid chromatography mass spectrometry method. For amoxicillin, the 90% confidence intervals of the test-to-reference ratios for Cmax, AUC0–t, and AUC0–∞ were 97.38–108.77%, 94.81–103.99%, and 94.66–104.03%, respectively. For clavulanic acid, the corresponding 90% confidence intervals were 96.21–115.11%, 91.31–109.26%, and 91.97–109.48%. All values fell within the accepted bioequivalence range of 80–125%. No adverse event was reported during the study. Bioequivalence and good tolerability were demonstrated between the test and reference products containing amoxicillin 875 mg and clavulanic acid 125 mg in healthy Vietnamese subjects.